Pengaruh Pemberian Beberapa Jenis Yogurt Komersial terhadap Jumlah Profil Darah Tikus (Rattus norvegicus) yang Diinduksi Diabetes Melitus - Febriani, Husnarika; Ulfa, Syarifah Widya; Butar-Butar, Tri Novitashari (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Diabetes mellitus is a metabolic disorder that occurs due to inadequate insulin levels or insulin resistance which leads to hyperglycemia. Handling hyperglycemia conditions in diabetes mellitus is very necessary, one of which is by consuming healthy and nutritious food. The aim of this research is to determine the results of total antioxidant levels in types of yogurt which can have an influence on the blood profile of white rats (Rattus norvegicus) with diabetes mellitus. This research used white rats (Rattus norvegicus) as experimental animals which were divided into 5 groups (K+: normal type, K-: negative type (alloxan), P1: type I yogurt brand (drinking yogurt), P2: type. yogurt brand II (yogurt set), P3: kel. yogurt brand III (stirred yogurt) with 5 treatment repetitions each. Yoghurt was given using the oral sonde technique to the experimental animals. Blood samples from the experimental animals were taken through the orbital sinus using hematocrit. Profile Rat blood was tested using a hematology analyzer. The data obtained were analyzed using one-way ANOVA and Duncan's test with a significance level of 0.05. Statistical results showed that there were significant differences (p < 0.05) in each treatment group. Based on the average results erythrocytes, hemoglobin, leukocytes and platelets that brand III yogurt samples had a better level of improvement than the others. This is also in line with the results of testing antioxidant levels in brand III yogurt, namely 51.38 ppm, which means the antioxidant levels are strong.